Major-Minor Tonality, Schenkerian Prolongation, and Emotion: A commentary on Huron and Davis (2012) - Parncutt, Richard (Empirical Musicology Review, 2013)
<span style="line-height: 115%; font-family: 'Times New Roman','serif'; font-size: 10pt; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-US">On average, melodies in minor keys have smaller intervals between successive tones than melodies in major keys - consistent with the emotional difference between major and minor (Huron, 2008). Huron and Davis (2012) additionally showed that a part of this difference is inherent in the structure of major and minor scales, in combination with typical patterns of transition between scale steps: If one takes a typical major melody and lowers scale steps 3 and 6 by a semitone, the average interval size is optimally reduced. I present an alternative theory of the origin of major and minor scales/keys and their emotional connotations. Huron’s (2006) data on scale-step transitions in typical melodies is consistent with Schenker’s (1922, 1935) idea that a piece of tonal music can be interpreted as a prolongation of its tonic triad (mediated by the Ursatz). The emotional difference between major and minor may ultimately and primarily depend on the third of the tonic triad in the psychological background. Major music may tend toward positive valence simply because emotionally positive music is more common than emotionally negative music, and major triads and keys are more common than minor. Minor music may tend toward negative valence simply because scale degrees 3 and 6 sound lower than expected, consistent with emotional cues in speech (Huron, 2008).